Estudio de prefactibilidad para la instalación e implementación de una granja de cuyes de la raza Perú en la Provincia de Trujillo - Wilson Carbajal, Emanuel Alexander (2010)
This project, Prefeasibility Study for the lnstallation and lmplementation of a farm in guinea pigs of the race "Peru" in the province of Trujillo; were applied in based on a sample of 84 restaurants located in the Districts of Huanchaco, Moche and Victor Larco; to determine the demand The Market survey found that for the 2011 there will be a demand for 67609 guinea pigs, taking a significant growth until the 2020 in 197878 guinea pigs, the project aims to have a stake of 11.2 per cent for the first year to 11.41 for the 2020. The upbringing begin with the purchase of 600 guinea pigs females and 75 guinea pigs male, the first year the farm will have a production of 2703 guinea pigs, up from the fifth year an average production of 14192 guinea pigs ayear The total investment amounts to $ 77881.83; fragmenting into fixed investment tangible$ 53061.3, fixed investment intangible$ 6953.07 and the working capital$ 17867.46 The results of the Economic Assessment Financia!, indicate that the Project is feasible to run with a Net Present Value of US$ 38426.20, an Interna! rate of return of 96.69%, a Benefit Cost of 1.89 anda period of recovery in investment of 7 years.